AL-QUR'ÂN YUFASSIRU BA'DHUHU BA'DHA ACCORDING TO BINTU SYÂTHI' - Syofrianisda Syofrianisda; Dewi Murni (SYAHADAH : Jurnal Ilmu al-Qur'an dan Keislaman, 2023)
Of the various forms of interpretation methods that exist and the application of these methods in a book of interpretation. The author sees that the rules of al-Qur'ân Yufassiru Ba'dhuhu Ba'dha, although already known by mufassir circles, are not systematic in their application. The application made between one mufassir and other mufassir does not have the same benchmark. That is, the principles of al-Qur'ân Yufassiru Ba'dhuhu Ba'dha are recognized in theory, but in practice they are still global. As an example of the application of the rules of al-Qur'ân Yufassiru Ba'dhuhu Ba'dha in the books of bi al-mâtsur interpretations. Among them, the book al-Dur al-Mânsur and Jami' al-Bayân. These three commentary books, although they agree that al-Qur'ân Yufassiru Ba'dhuhu Ba'dha. However, in applying the principles of the Koran, Yufasîrru Bâ'dhuhu Bâ'dha has different portions. What is the form of the provisions and criteria for which verses will be interpreted with other verses or to what extent there is no limit to the application of this rule in the related book. So how the proper application of this rule is still not systematic. This is the form of application of the rules of the Koran Yufasîrru Bâ'dhuhu Bâ'dha in the classical period.